2006
DOI: 10.1074/jbc.m505457200
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of a Circumscribed Recombination Hot Spot in HIV-1 after a Single Infectious Cycle

Abstract: Recombination is a major source of genetic heterogeneity in the human immunodeficiency virus type 1 (HIV-1) population. The main mechanism responsible for the generation of recombinant viruses is a process of copy choice between the two copies of genomic RNA during reverse transcription. We previously identified, after a single cycle of infection of cells in culture, a recombination hot spot within the gp120 gene, corresponding to the top portion of a RNA hairpin. Here, we determine that the hot region is circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…This is in agreement with studies showing that recombination rates depend on a complex set of factors, such as the availability of nucleotide (nt) substrates (25)(26)(27), the RNA template itself (7,12,28), overall sequence similarity (6,7,10,12), and local sequence context of recombining sequences (28)(29)(30). Using both in vitro assays and single-cycle HIV-1 vectors, recombination hot spots have been identified in the untranslated regions (UTRs) (30)(31)(32), in gag (29,33), and in env (28,34). However, only limited information on recombination is available within other regions of the HIV-1 genome (33).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…This is in agreement with studies showing that recombination rates depend on a complex set of factors, such as the availability of nucleotide (nt) substrates (25)(26)(27), the RNA template itself (7,12,28), overall sequence similarity (6,7,10,12), and local sequence context of recombining sequences (28)(29)(30). Using both in vitro assays and single-cycle HIV-1 vectors, recombination hot spots have been identified in the untranslated regions (UTRs) (30)(31)(32), in gag (29,33), and in env (28,34). However, only limited information on recombination is available within other regions of the HIV-1 genome (33).…”
supporting
confidence: 65%
“…There have been many studies showing that even in the absence of selection, recombination does not occur randomly on the HIV-1 genome, highlighting the presence of additional factors governing the recombination process (11,19,(28)(29)(30)(31)(32)(33)(34)(35)59). However, many of these studies do not measure recombination rate in their natural genome context, or they measure recombination between highly divergent genomes that may not be most representative of the situation in vivo, where we expect recombination between closely related members of the viral quasispecies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, data from acceptor cleavage provide evidence that at least a portion of transfers occur as a consequence of acceptor invasion early in the region of homology. Single-stranded regions within the acceptor are proposed to favor the acceptor-cDNA interaction or "docking" step (42,46,60,66). In our template system, the absence of strong secondary structures within the proposed invasion site in the acceptor template correlated with efficient transfers compared with the poor transfers when the invasion site in the acceptor was part of a stable secondary structure (42).…”
Section: Discussionmentioning
confidence: 92%
“…Based on the example of the S1/S2 structure (Galetto et al 2004), one might predict that a recombination hot spot could be found within our proposed structure (Galetto et al 2006). Recombination breakpoints have been found in nucleotide region 230-330, i.e., in the sequence that folds to the predicted structure, between the pol gene sequences from different subtypes, such as between subtypes A and B, A and D, and B and D, as well as between B and F (Quarleri et al 2004;Yang et al 2004;Sa Filho et al 2005).…”
Section: Role Of the Rna Secondary Structurementioning
confidence: 99%